A Phase I Study to Evaluate the Pharmacokinetics and Safety of Cabotegravir in Adults With Severe Renal Impairment and Healthy Matched Control Participants. Issue 5 (27th February 2019) - Parasrampuria, Ridhi; Ford, Susan L.; Lou, Yu; Fu, Caifeng; Bakshi, Kalpana K.; Tenorio, Allan R.; Trezza, Christine; Spreen, William R.; Patel, Parul
Abstract: This study investigates the impact of severe renal impairment on the pharmacokinetics of cabotegravir, an investigational HIV‐1 integrase inhibitor. This was a phase I, open‐label, parallel‐group, multicenter study conducted in 8 participants with severe renal impairment (creatinine clearance <30 mL/min; no renal replacement therapy) and 8 healthy participants (creatinine clearance >90 mL/min; 2 women/group; 6 men/group) matched for sex, age (±10 years), and body mass index (±25%). Participants received a single 30‐mg oral cabotegravir tablet to determine total and unbound plasma cabotegravir concentrations. Arithmetic and geometric least squares means were calculated, and cabotegravir noncompartmental pharmacokinetic parameters were compared using geometric least squares mean ratios with 90% confidence intervals. Safety was assessed throughout the study. Geometric least squares mean ratios (90% confidence intervals) were 0.97 (0.84–1.14) for area under the plasma concentration‐time curve extrapolated to infinity, 1.01 (0.87–1.17) for maximum observed plasma concentration, 1.31 (0.84–2.03) for unbound cabotegravir 2 hours after dosing, and 1.51 (1.19–1.92) for unbound cabotegravir 24 hours after dosing. All adverse events were grade 1, except grade 3 lipase elevation in a participant with renal impairment. Severe renal impairment did not impact plasma cabotegravir exposure, and cabotegravir may be administered without dose adjustment in renal impairment among patients not receiving renal replacement.